(untitled) (Baghdad Science Journal, 2025)
The research work was conducted to investigate the effect of oral administration of aqueous extract of turmeric at doses of (5, 10) mg/kg body weight for two weeks daily by determining the genotoxic effect (mitotic index), evaluation of immunological effect (IgG, IgM, IgA, C3, C4) and measuring fertility hormones (follicles stimulation hormone/FSH, lutenising hormone/LH) levels with histological examinations of female albino swiss mice ovaries in comparison with control (normal saline). A clear effect in increasing mitotic activity was reveled for both doses in comparison with control. Results also showed a significant increase in the value of all immunological parameters at both doses, in comparison with control. Also, obvious raise was seen in the levels of FSH and LH hormones for both doses when compared with normal saline treated mice with no significant damage seen in female ovaries tissue, in fact, there were certain changes in mice ovaries tissue which were represented by increasing in the numbers of primary and secondary follicles and in the numbers of corpus luteum at both doses also.